2014
DOI: 10.1186/1710-1492-10-1
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and feasibility of oral immunotherapy to multiple allergens for food allergy

Abstract: BackgroundThirty percent of children with food allergy are allergic to more than one food. Previous studies on oral immunotherapy (OIT) for food allergy have focused on the administration of a single allergen at the time. This study aimed at evaluating the safety of a modified OIT protocol using multiple foods at one time.MethodsParticipants underwent double-blind placebo-controlled food challenges (DBPCFC) up to a cumulative dose of 182 mg of food protein to peanut followed by other nuts, sesame, dairy or egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 35 publications
6
125
0
1
Order By: Relevance
“…Changes in Th17 cells correlate with asthma induction, making it important to analyze Th-17 proteins such as TNF-α, IL-6, and IL-1β [40]. We previously reported a correlation between TNF-α gene expression [41] and protein levels [42] and the induction of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in Th17 cells correlate with asthma induction, making it important to analyze Th-17 proteins such as TNF-α, IL-6, and IL-1β [40]. We previously reported a correlation between TNF-α gene expression [41] and protein levels [42] and the induction of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous OIT studies with multiple food allergens are currently underway, some with and some without coadministration of omalizumab. To date, preliminary data from one study demonstrated similar reaction rates and efficacy comparing monotherapy with peanut to OIT based on up to 5 foods [54], while a second Phase 1 study demonstrated successful desensitization to multiple foods using rush OIT after pretreatment with omalizumab. Reaction rates were relatively low (median of 3.2 reactions per 100 doses) [55].…”
Section: Oit To Other Foods and Multiallergen Oitmentioning
confidence: 99%
“…Rates (3.3% for single and 3.7% for multi-food) and severity of reactions (with 2 participants requiring epinephrine in each group) did not differ significantly between the two groups. These results suggest that desensitization and immunomodulation may be achieved with multi-food OIT, with a similar safety profile to singlefood OIT [60] . Multi-food OIT, given its potential to be useful in the large portion of food-allergic individuals sensitized to multiple foods, certainly deserves further investigation.…”
Section: Multi-food Oitmentioning
confidence: 67%